NALISIS HUBUNGAN KUALITAS PELAYANAN DAN PROMOSI DENGAN KEPUTUSAN NASABAH DALAM MENABUNG PADA PT BPR FAJAR WARAPASTIKA LAMPUNG TIMUR - Rita Irviani; Elvina Febri Nadirsyah (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2018)
The purpose of this study is to empirically examine how the relationship of service quality and promotion with customer decisions in saving at PT BPR Fajar Warapastika. This research uses primary data and secondary data. Primary data is data collected directly by researchers from the source. Primary data is taken by distributing questionnaires to customers of PT. BPR Fajar Warapastika. While secondary data obtained from the literature that supports research, both from books, the internet, data from PT. BPR Fajar Warapastika, and so on. Data analysis techniques using the calculation of Multiple Correlation, T Test and F Test. After the calculation, the results obtained R = 0.299, this shows a low level of relationship. Then in the T Test all independent variables have a significant effect on the dependent variable. Evidenced by the acquisition of sig. which is smaller than 0.05 and the calculated t value is greater than t table (1,975).